Literature Review: Baby Massage Sebagai Terapi Komplementer Diare pada Balita - Diah Karina Wibowo; Ervina Damayanti; Ramadhan Triyandi; Muhammad Fitra Wardhana Sayoeti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Diarrhea remains a leading cause of mortality among toddlers in Indonesia, with a prevalence reaching 4,9%. In addition to pharmacological management through LINTAS DIARE, non-pharmacological therapies such as baby massage are increasingly being implemented as supportive interventions that families can perform to accelerate recovery. This study aims to examine the effectiveness of baby massage as a complementary therapy in reducing the frequency and intensity of diarrhea in toddlers. The method used involved identifying relevant articles from Google Scholar and Semantic Scholar databases using appropriate keywords. Based on the 6 articles obtained, baby massage significantly (p = 0,000) reduces the frequency and intensity of diarrhea through vagus nerve stimulation, which optimizes intestinal peristalsis and nutrient absorption. Beyond improving defecation patterns, this therapy is proven to significantly increase infant weight, accelerate motor development through central nervous system stimulation, and enhance sleep quality and comfort.